2021
DOI: 10.1016/j.apenergy.2021.116769
|View full text |Cite
|
Sign up to set email alerts
|

Pay-as-you-go liquefied petroleum gas supports sustainable clean cooking in Kenyan informal urban settlement during COVID-19 lockdown

Abstract: Graphical abstract

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 38 publications
(51 reference statements)
1
28
0
Order By: Relevance
“…Malakar et al (2018) found that LPG-using households were less reliant on farms and forests and many also had women earning income, with which they had purchased LPG. The latter observation about income earned by women was echoed by Shupler et al (2021) in their analysis of pay-as-you-go LPG in Nairobi, reinforcing participation of women in income generation as an important step toward universal access.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Malakar et al (2018) found that LPG-using households were less reliant on farms and forests and many also had women earning income, with which they had purchased LPG. The latter observation about income earned by women was echoed by Shupler et al (2021) in their analysis of pay-as-you-go LPG in Nairobi, reinforcing participation of women in income generation as an important step toward universal access.…”
Section: Discussionmentioning
confidence: 99%
“…Nairobi is one of the first cities to market pay-as-you-go LPG. A recent study collected data from 426 pay-as-you-go LPG customers living in an informal settlement in Nairobi from January 2018 to June 2020 (Shupler et al 2021). Seven interviewed participants reported feeling safer cooking with LPG because of the marketer's tighter control of the cylinders-one commented that if a cylinder were to start leaking, the marketer would remotely detect the leak and shut off the gas.…”
Section: Lumpiness Of Fuel Purchasementioning
confidence: 99%
See 1 more Smart Citation
“…The understanding and the need for higher adoption of cleaner fuel and its effect of education becomes even more pertinent in the present scenario as the outbreak of the COVID-19 across the world may not only reduce the pace of clean fuel adoption, but also threatens to reverse the initial gains in energy transition. Recent studies in the context of Africa find that the pandemic induced income shocks led to substitution of LPG with cheaper polluting fuels like coal and kerosene by households (Shupler et al, 2021a). Given that the use of solid fuel is mostly concentrated in the Global South, any further movement down the energy ladder can potentially widen the energy gap between the low and middle income and high income countries apart from increasing inequality between rich and poorer within these developing economies.…”
Section: Discussion In the Light Of The Covid-19 Pandemicmentioning
confidence: 99%
“…This along with a significant fall in global fossil fuel prices especially during 2020 can possibly become a major hurdle for clean energy adoption as the relative price of using clean energy sources have gone up significantly (Hoang, 2021). While Smith et al (2021) argue that the fall in the price of fossil fuel and the COVID-19 pandemic may not affect the climate change mitigation efforts by the countries, both macro and microeconomic evidence largely indicates that the pandemic poses a real threat of delaying in the energy transition to cleaner fuel in the Global South (Ravindra et al 2021;Shupler, 2021a). However, it is worth noting that a recent study by Shupler et al (2021b) find that the pay as you go LPG users in Kenya were less likely to reduce cooking time during lockdown than conventional LPG cylinder users highlighting the need to deploy technology based solutions to ensure that the fragile gains towards clean energy adoption do not get reversed and in fact the household energy transition trajectory gets accelerated in the post-covid recovery period.…”
Section: Discussion In the Light Of The Covid-19 Pandemicmentioning
confidence: 99%